Impact of high cholesterol and endoplasmic reticulum stress on metabolic diseases: An updated mini-review - SÖZEN, AHMET ERDİ; KARTAL ÖZER, NESRİN (ELSEVIER SCIENCE BV, 2017)
Endoplasmic reticulum (ER) is the major site of protein folding and calcium storage. Beside the role of ER in protein homeostasis, it controls the cholesterol production and lipid-membrane biosynthesis as well as surviving and cell death signaling mechanisms in the cell. It is well-documented that elevated plasma cholesterol induces adverse effects in cardiovascular diseases (CVDs), liver disorders, such as non-alcoholic fatty liver disease (NAFLD), non-alcoholic steatosis hepatitis (NASH), and metabolic diseases which are associated with oxidative and ER stress. Recent animal model and human studies have showed high cholesterol and ER stress as an emerging factors involved in the development of many metabolic diseases. In this review, we will summarize the crucial effects of hypercholesterolemia and ER stress response in the pathogenesis of CVDs, NAFLD/NASH, diabetes and obesity which are major health problems in western countries.
Keywords: Endoplasmic reticulum stress; High cholesterol; Cardiovascular diseases; Non-alcoholic fatty liver disease; Non-alcoholic steatosis hepatitis; UNFOLDED PROTEIN RESPONSE; ATTENUATES CARDIOMYOCYTE DEATH; ER STRESS; HEPATIC STEATOSIS; CELLULAR STRESS; ACTIVATION; EXPRESSION; PHOSPHORYLATION; APOPTOSIS; ATHEROSCLEROSIS